SYNTACTIC TRANSFORMATIONS IN TRANSLATING A SCIENCE ARTICLE - Mykhailenko, O. (Linguistic and Conceptual Worldviews, 2020)
Publishing the research results in a science article with an international professional journal is an optimal way of sharing the information about newest discoveries in the world of science and technology. Not all scientists have a command of English sufficient for writing a science article, in compliance with high language requirements of leading scientific journals. So, the services of highly-qualified translators of scientific texts into English are in great request, and Ukraine is not an exception. Apart from the basic components of translator's professional competence, especially important is the knowledge of norms of the modern English language scientific discourse. A translator of scientific texts is to have solid knowledge of grammar of source and target languages, regularities in rendering grammar forms and constructions, translation transformations. The largest number of grammar problems in translation is related to understanding the syntactic structure of sentences and a translator's ability to make necessary transformations. Our research was aimed at analyzing the role of syntactic transformations in reaching the adequacy in English translation of Ukrainian language articles from scientometric journals. The analysis proved that the majority of syntactic transformations were used to bring the source text in conformity with the target language norms. The measure of translation transformations was generally adequate, though there were cases of non-use of syntactic transformations where they were necessary. Grammar literalism was also observed, due to translator's insufficient understanding of the sentence structure, lack of knowledge of grammar peculiarities of the target language and translation solutions available for solving a particular translation problem. A translator of scientific texts should be particularly attentive to the syntax of the original sentence, analyse it properly, identify grammar phenomena that may cause translation problems and may need syntactic transformations, and build a translated sentence in accordance with the science language norms.
Keywords: science article, scientific language norms, Ukrainian language, English language, syntactic transformation, translation technique